Prohibition of age discrimination in the labour market - Vaitkeviciute, Agne (Delavci in delodajalci, 2017)
This Article analyses the case of Finland in the context of European Union from the perspectives of general non-discrimination law and labour law, and the functioning of legal anti-discriminatory provisions from the sociological point of view. It is maintained that age anti-discriminatory provisions in general and specific (labour-law-related) legislation, in collective agreements and soft law documents as labour-lawrelated instruments compose an extensive background for preventing age discrimination in employment in Finland. It is asserted that the existence of age anti-discriminatory provisions interacts with the objective to ensure longer working careers and aims at improving the chances of the elderly to stay in employment after reaching retirement age.
Keywords: delovno pravo; diskriminacija; Finska; preprečevanje; starejši ljudje; trg delovne sile; zaposleni